2019
DOI: 10.36346/sarjps.2019.v01i03.001
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Prevalence of Trauma Cases Visited At Emergency OPD in Dilla University Referal Hospital from April 20, 2008–May 20, 2008 E.C

Abstract: Background: Injuries and violence pose a major public health and developmental problem globally. Each year over 5 million people around the world die as a result of injury. Injuries are ranked among the leading cause of death and disability particularly in low income and middle income countries where they are growing insignificance, largely as a consequences of epidemiologic, demographic and socioeconomic transitions. Moreover, it is in these very setting that the vital statistics and routine health informatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…20 Evidence showed that 50.0% of hospital visits from trauma were minor injuries. 21 On stratification of systemic injuries, 8 (25%) of patients who sustained head injury died, which showed higher mortality rate in line with lower mental status level of the patient on presentation. Patients with GCS score of 15/15 have 96% lower chance of dying compared with patients having lower GCS score, AOR=0.04, 95% CI 0.00 to 0.46.…”
Section: Discussionmentioning
confidence: 99%
“…20 Evidence showed that 50.0% of hospital visits from trauma were minor injuries. 21 On stratification of systemic injuries, 8 (25%) of patients who sustained head injury died, which showed higher mortality rate in line with lower mental status level of the patient on presentation. Patients with GCS score of 15/15 have 96% lower chance of dying compared with patients having lower GCS score, AOR=0.04, 95% CI 0.00 to 0.46.…”
Section: Discussionmentioning
confidence: 99%
“…Road traffic accidents (RTAs), personal conflict, interpersonal violence, and work-related accidents are the most common causes of fractures. 2 , 3 The upper extremity, head and hand, multiple parts, and lower extremity were the most commonly reported types of fractures based on the body parts involved. 4…”
Section: Introductionmentioning
confidence: 99%
“…3 , 4 Different studies reported that the cause of fractures in LMIC was road traffic accidents, personal conflict, interpersonal violence, and work related accidents. 5 , 6 Based on body parts involved; lower extremity, head and hand, multiple part and upper extremity were commonly reported types of fracture. 7…”
Section: Introductionmentioning
confidence: 99%